Renal Function and Bone Loss in a Cohort of Afro‐Caribbean Men. (16th June 2015) - Kuipers, Allison L; Egwuogu, Heartley; Evans, Rhobert W; Patrick, Alan L; Youk, Ada; Bunker, Clareann H; Zmuda, Joseph M
ABSTRACT: Poor renal function is associated with increased rates of bone loss and osteoporotic fractures in Caucasian men. The importance of kidney function for skeletal health in African ancestry men, who are a population segment with a high prevalence of chronic kidney disease as well as high peak bone mass, is not well known. We examined the relationship between estimated glomerular filtration rate (eGFR) and rates of bone loss in a large population cohort of otherwise healthy Afro‐Caribbean men aged 40 years and older. Dual X‐ray absorptiometry of the proximal femur and quantitative computed tomography of the proximal radius and tibia were obtained approximately 6 years apart. We calculated eGFR from serum creatinine that was measured in fasting samples in 1451 men. Impaired kidney function (IKF, eGFR<60 ml/min/1.7 m 2 ) was observed in 8.6% of the cohort. The relationship between IKF and baseline BMD and annualized rate of change in BMD was analyzed controlling for potentially important confounders. IKF was not associated with baseline BMD. In contrast, men with IKF experienced a rate of decline in areal BMD at the total hip, femoral neck and trochanter and cortical volumetric BMD compared to those with normal kidney function (p<0.05 for all). Impaired kidney function was not associated with changes in trabecular volumetric BMD. In conclusion, poorer kidney function is associated with accelerated bone loss among otherwise healthy Afro‐Caribbean men even after controlling for age and other important medical and lifestyle related variables. © 2015 American Society for Bone and Mineral Research.